Drag ur den finländska judenhetens historia - Harviainen, Tapani (Nordisk judaistik, 1985)
The earliest mention of Jewish visitors in Finland dates back to 1782. At that time Finland was a part of Sweden, and Swedish legislation only allowed Jews to settle in four cities of the mother country. When Finland was incorporated into Russia in 1809 as a consequence of the Napoleonic wars, Swedish laws remained in force in the Grand Dutchy, and they prohibited the entry of Jews. However, Jewish soldier came to the fortress of Sveaborg off Helsinki, to Viipuri and other garrison towns with the Russian army. In the 1920’s and 30’s the number of Jews in Finland reached a peak of approximately 2000. During the Second World War Jewish citizens served in the army and in other duties side by side with other Finns. There were approximately 150 Jewish refugees in Finland&&eight were deported to the Gestapo in 1942. The main problems of the Jewish congregations today are depopulation, the increasing average age of the members, general secularism, and mixed marriages.